CRL4DCAF1 ubiquitin ligase regulates PLK4 protein levels to prevent premature centriole duplication - Großmann, Josina; Kratz, Anne-Sophie; Kordonsky, Alina; Prag, Gali; Hoffmann, Ingrid (Life science alliance, 2024)
Centrioles play important roles in the assembly of centrosomes and cilia. Centriole duplication occurs once per cell cycle and is dependent on polo-like kinase 4 (PLK4). To prevent centriole amplification, which is a hallmark of cancer, PLK4 protein levels need to be tightly regulated. Here, we show that the Cullin4A/B-DDB1-DCAF1, CRL4DCAF1, E3 ligase targets PLK4 for degradation in human cells. DCAF1 binds and ubiquitylates PLK4 in the G2 phase to prevent premature centriole duplication in mitosis. In contrast to the regulation of PLK4 by SCFβ-TrCP, the interaction between PLK4 and DCAF1 is independent of PLK4 kinase activity and mediated by polo-boxes 1 and 2 of PLK4, suggesting that DCAF1 promotes PLK4 ubiquitylation independently of β-TrCP. Thus, the SCFSlimb/β-TrCP pathway, targeting PLK4 for ubiquitylation based on its phosphorylation state and CRL4DCAF1, which ubiquitylates PLK4 by binding to the conserved PB1-PB2 domain, appear to be complementary ways to control PLK4 abundance to prevent centriole overduplication.
Online veröffentlicht: 15. März 2024
Im Titel ist der Ausdruck "DCAF1" hochgestellt
Gesehen am 23.07.2024